Microbial diversity formed and maintained through substrate feedback regulation and delayed responses induced by Low-Dose Ionizing Radiation. (November 2021) - Yang, Xinbin; Li, Shuaishuai; Song, Ganyu; Xu, Xinming; Hu, Dawei
Abstract: Microbial diversity is essential for the maintenance of the normal structure and function of bioregenerative life support systems (BLSS). As a typical nutrient-deficient environment (NDE), the BLSS does not provide sufficient types of available substrates for microbial communities, and its internal microbial diversity is usually not high due to interspecific competitive exclusion. However, it is reported that microbial diversity is abnormally high in the International Space Station (ISS) after long-term exposure to low-dose ionizing radiation (LDIR). It remains a mystery why LDIR leads to the formation and maintenance of high microbial diversity. In this study, a series of artificial microbial communities have been cultivated in NDE without and with LDIR, respectively. These communities are composed of three common microbial species ( Escherichia coli, Bacillus subtilis and Pseudomonas aeruginosa ) in the ISS. By comparing and analyzing the differences in the microbial physiological and behavioral response characteristics in the two scenarios, a reasonable hypothesis was put forward to elucidate the formation and maintenance mechanisms of high microbial diversity in NDE with LDIR. Then a set of kinetic models were developed based on this hypothesis, observed phenomena, and experimental data. Finally, these kinetic models were sufficiently validated and the hypothesis was fully confirmed through large-scale digital simulations. Briefly, two fundamental succession mechanisms of the microbial communities are supposed to exist in NDE with LDIR: substrate-based negative feedback regulation (SNFR) and microbial delayed responses. These two decisive succession mechanisms can give rise to asynchronously convergent fluctuations of microbial populations and significantly alleviate the interspecific competitions. Such a species-for-quantity strategy drives the microbial communities to form and maintain species diversity with higher richness and evenness. This study can lay the theoretical foundation and provide new ideas for the construction of advanced BLSS featured with more robust structures and stronger function. Highlights: Proposed a hypothesis on microbial diversity induced by low-dose ionizing radiation. Identified four delayed responses that significantly reduce strength of interspecific competitions. Developed a set of highly valid kinetic models of microbial diversity formation and maintenance. Predicted the emergence patterns of synchronously convergent fluctuations of microbial populations and proved it.